Changes in Conceptualizations During Assertiveness Training - Comeau, Nancy; Hiebert, Bryan (Canadian Journal of Counselling and Psychotherapy, 2011)
Conceptualizations regarding the characteristics of assertive people were assessed at the beginning and end of a group Assertiveness Training program. Participants who demonstrated the greatest gain in assertiveness also demonstrated the largest shifts in conceptualizations. Moreover, substantial differences in conceptualizations were observed between participants who became more assertive and those who did not. The results suggest that greater emphasis in assertiveness training should be placed on developing an intergrated conceptual base for assertive characteristics.